REPORT OF COMMITTEE ON PROFESSIONAL EDUCATION IN ACCOUNTING. - Heaton, Herbert; Herbert, Leo; Kell, Walter G.; Warner, George S.; Zlatkovich, Charles T.; Wyatt, Arthur R. (The Accounting Review, 1959)
Abstract The Committee on Professional Education in Accounting has been considering, for the past two years, the general area of educational preparation for a career in accounting. The committee believes that its primary problem was to establish a concept of professional education for a career in accounting. This report is a summary of the committee's discussions and deliberations concerning the nature, objectives and implementation of professional education in accounting. The Report of Standards Rating Committee of the American Accounting Association' contained the following statement on objectives of the education of the accountant: "Three ultimate objectives of education for professional accounting are educating the citizen, education in business and education in accounting. A program of professional education should provide the student with the theoretical background necessary to proper interpretation of practical problems. The major objective of technical accounting coverage in a professional program should be to provide the graduate with the foundation to recognize, interpret and analyze the complex and specialized problems to be faced in his future career.